The development and institutionalisation of knowledge and knowledge-sharing practices relating to the management of healthcare risk waste in a home-based care setting - Masilela, Mapula Priscilla (Rhodes University, Faculty of Education, Department of Education, 2017)
Improperly managed healthcare risk waste is associated with environmental degradation due to its potential to pollute air, land and water; it also poses a public health threat due to risks to community members (adults and children) who may find themselves exposed to waste that has been disposed of improperly. Despite these obvious environmental health risks, there is little information or legislative guidance on how to effectively manage the healthcare risk waste generated by community health workers who move from house to house and do not operate out of a fixed clinic with formal waste management facilities. This poses a challenge for municipal environmental health practitioners who are mandated to ensure compliance and to monitor the management of healthcare risk waste by community home-based care facilities. This educational study looks at how the knowledge held by environmental health practitioners influences knowledge-sharing practices and management of healthcare risk waste by community health workers, and how these knowledge-sharing practices can be developed and institutionalised. The study takes an interventionist approach within the social constructionist tradition. Cultural- Historical Activity Theory (CHAT) and expansive learning provide the theoretical and methodological framework to surface systemic tensions and contradictions affecting knowledgesharing and healthcare risk waste management practices. A series of Change Laboratory Workshops using the Developmental Work Research methodology enabled a twenty-seven month expansive learning process with selected municipal employees and community health workers in a small South African city. The study found that employees (such as environmental health practitioners and waste inspectors) working in municipal activity systems knew very little about the forms and functions of community home-based care facilities in their municipality. As such, their knowledge-sharing practices about the management of healthcare risk waste were restricted and generally unsystematic, which in turn contributed to inappropriate and often haphazard healthcare risk waste management practices by community health workers. As an interventionist project, the study concluded that the participatory, expansive learning process it initiated had built knowledge-sharing networks, enabled professional boundary crossing and potentially institutionalised better knowledge-sharing practices relevant to the effective management of healthcare risk waste.
Keywords: Medical wastes -- Management -- South Africa -- West Rand; Medical wastes -- Government policy -- South Africa -- West Rand; Environmental health -- South Africa -- West Rand; Environmental health -- Administration -- South Africa -- West Rand; Environmental health -- Government policy -- South Africa -- West Rand